2014
DOI: 10.1186/1471-2164-15-124
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and functions of a multipartite genome of the methylotrophic bacterium Paracoccus aminophilus JCM 7686, containing primary and secondary chromids

Abstract: BackgroundParacoccus aminophilus JCM 7686 is a methylotrophic α-Proteobacterium capable of utilizing reduced one-carbon compounds as sole carbon and energy source for growth, including toxic N,N-dimethylformamide, formamide, methanol, and methylamines, which are widely used in the industry. P. aminophilus JCM 7686, as many other Paracoccus spp., possesses a genome representing a multipartite structure, in which the genomic information is split between various replicons, including chromids, essential plasmid-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 86 publications
2
59
0
Order By: Relevance
“…We have identified the first example of an MTase in an Alphaproteobacteria phage that could methylate the GANTC sequence in a temperate phage, ⌽Pam-6, of P. aminophilus JCM 7686. We have also demonstrated that two other putative prophages in the P. aminophilus JCM 7686 genome encoded MTases with the same specificity as the host CcrM (65). Here, we report another example of this interesting phenomenon.…”
Section: Dziewit Et Alsupporting
confidence: 52%
See 1 more Smart Citation
“…We have identified the first example of an MTase in an Alphaproteobacteria phage that could methylate the GANTC sequence in a temperate phage, ⌽Pam-6, of P. aminophilus JCM 7686. We have also demonstrated that two other putative prophages in the P. aminophilus JCM 7686 genome encoded MTases with the same specificity as the host CcrM (65). Here, we report another example of this interesting phenomenon.…”
Section: Dziewit Et Alsupporting
confidence: 52%
“…We have shown previously that the three m 6 A MTases (JCM7 686_1231, JCM7686_2255, and JCM7686_2934) identified in the prophage regions of the genome of Paracoccus aminophilus JCM 7686 methylated the GANTC sequence (65). It is noteworthy that all of the genes coding for phage MTases (⌽LM21 as well as ⌽Pam-2, ⌽Pam-4, and ⌽Pam-6 of P. aminophilus) are localized within the predicted replication module.…”
Section: Fig 4 Comparison Of Restriction Patterns Of Dammentioning
confidence: 95%
“…Genome analyses of many genera, such as Bacillus, Enterococcus, Listeria, Mannheimia, Paracoccus, Staphylococcus and Streptococcus revealed that polylysogeny is a common phenomenon (Dziewit et al, 2014a;Goerke et al, 2009;Niu et al, 2015). Recently, we have also identified a polylysogenic Sinorhizobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, besides other bacterial species, R. gelatinosus might play an essential role in conditioning the sediment surface, facilitating subsequent diatom settlement and development, as described for other heterotrophic bacteria. 65 Moreover, the fast growth and potential for high EPS production of R. capsulatus and P. aminophilus [95][96][97] may lead to a solid biofilm fundament tightly attached to the sediment grains, especially in crucial early developmental stages. This could be of major structural importance for the overall biofilm system and lead to higher biofilm stability.…”
Section: Role Of Microorganisms In Biofilm Matrixmentioning
confidence: 99%